Phytochemical screening of Sargassum sp and in vitro seed germination test - Baharudin, Siti Fatimah; Alimon, Hasimah Binti; Daud, Norhayati Binti (Universitas Pendidikan Indonesia, 2019)
The aim of the present paper is to evaluate the phytochemical screening of Sargassum sp and also to investigate the effect of its crude extracts on seed germination and seedling development of Capsicum annum. The samples were dried and made to coarse powder and stored at -20Â°C for further analysis. Crude extracts were prepared using three different solvents (DCM, methanol and hexane).Â Â Different concentrations of crude extracts were prepared in solid medium using MS basal media and germination tests were carried out in vitro. High concentration (50ul/mL) of hexane extract exhibited most promoting effect on seed germination and seedling development of Capsicum annum followed by methanol (50ul/mL) and DCM (50ul/mL). The presence of micro and macro nutrients, vitamins, growth hormones and other constituents in the seaweed extract might be very much useful to the crop but their concentration should be appropriate to enhance growth and productivity. It may be concluded that Sargassum extracts could serve as cost effective and eco-friendly product for sustainable agriculture.